Síntese e caracterização de nanocompósitos de ferrita de cobalto/carvão ativado à partir de copolímeros de estirenodivinilbenzeno sintetizados com óleo de soja - Barbosa, Carolina Freire (2014)
In this work, activated carbon beads were prepared through carbonization of styrene-divinylbenzene (Sty-DVB) copolymers synthesized in the presence of soybean oil as diluent and cobalt ferrite nanoparticles dispersed in the organic phase. Firstly, a cobalt ferrite gel was prepared through co-precipitation technique with posterior surfactant action by oleic acid. The copolymer and the composites containing cobalt ferrite were obtained through suspension polymerization. Four matrixes were obtained, which have the following differences: the cobalt ferrite content (2 or 5 %), the amount of hydroxyethylcellulose used in the synthesis and the realization or not of a purification step before thermal treatments. Soybean oil was chosen as diluents in order to evaluate its effects on the synthesized materials considering the polymerization possibility due fat acid unsaturations and its low volatility. All synthesized materials were characterized by the following analysis: DRX, FTIR, TGA, nitrogen adsorption measurements (specific surface area, pore volume and pore size distribution), MEV and catalytic activity in the ethyl-benzene dehydrogenation reaction. Further, the composites had metal content evaluate by AAS. The soybean oil and the ferrite gel had a strong influence on the textural properties of copolymers and their respective activated carbons. All obtained activated carbons were active in relation to ethylbenzene dehydrogenation reaction. However, the activated carbon obtained from pure copolymer, i.e., without cobalt ferrite, presented the highest specific surface area, catalytic activity and selectivity. This catalyst also had the best stabilization of catalytic properties during evaluated reaction time.